2019
DOI: 10.1097/mat.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inflow Cannula Angle on the Intraventricular Flow Field of the Left Ventricular Assist Device–Assisted Heart: An In Vitro Flow Visualization Study

Abstract: Previous studies have identified left ventricular assist device (LVAD) inflow cannula (IC) malposition as a significant risk for pump thrombosis. Thrombus development is a consequence of altered flow dynamics, which can produce areas of flow stasis or high shear that promote coagulation. The goal of this study was to measure the effect of IC orientation on the left ventricle (LV) flow field using a mock circulatory loop, and identify flow-based indices that are sensitive measures of cannula malposition. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…When LVAD support is added to the failing heart, the boost to cardiac output provides restoration of end‐organ perfusion, but the incidence of serious thromboembolic complications increases several‐fold. Previous studies of the LV velocity field during LVAD support have shown that increased cannula insertion depth does not alter the formation of the large CW diastolic vortex, but reduces its circulation and KE during the cardiac cycle . The CCW vortex is smaller and exhibits complex behavior, exhibiting a flow split at 3 cm of insertion depth.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…When LVAD support is added to the failing heart, the boost to cardiac output provides restoration of end‐organ perfusion, but the incidence of serious thromboembolic complications increases several‐fold. Previous studies of the LV velocity field during LVAD support have shown that increased cannula insertion depth does not alter the formation of the large CW diastolic vortex, but reduces its circulation and KE during the cardiac cycle . The CCW vortex is smaller and exhibits complex behavior, exhibiting a flow split at 3 cm of insertion depth.…”
Section: Discussionmentioning
confidence: 88%
“…12 In addition, a decrease in both average and systolic velocities were observed within the inflow cannula. 12 An increase in the insertion length of the inflow cannula into the LV was also associated with increased flow stasis and reduced pulsatility. 13 In all of these previous studies, the regions of greatest flow disturbance are produced by the protrusion of the inflow cannula into the LV and are affected by the mechanical interaction of the native heart and the LVAD.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations